SYNTHESIS OF NEW METHACRYLATES OF 6-HYDROXYAURONES (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2016)
Natural aurones and their synthetic analogues exhibit antibacterial, antiviral, antioxidant and anti-cancer activity. We have known thatsynthetically derived aurone Z-configuration of the exocyclic double bond and capable of photoisomerization in the corresponding E-isomers in their UV irradiation. For creation novel polymers of special application, by using condensation reaсtion of 6-hydroxybenzofuran-3-one with benzaldehydes in the mixture of ethanol, DMF and alkalis were synthesized new (2Z)-6-hydroxy-2(4-R-benzeliden)-1-enzofuran-3(2H)-ones. Then their acylation by methacryloyl chloride and at the present triethylamine were synthesized new methacrylic derivatives of (2Z)-6-hydroxy-2(4-R-benzeliden)-1-benzofuran-3(2H)-ones.So, we have proposed simple and effective method for the synthesis of (2Z)-6-metakryloksy-2-(4-R-benzyliden)-1-benzofuran-3(2H)-ones with high yields at very mild conditions. New methacrylic derivatives are solids with relatively high melting points, resistant while maintaining the air and not deeply colored crystalline monomers.The structure of synthesized substances were characterized and evaluated by 1HNMR, IR spectroscopy. Then we will investigate their polymerization activity of the homo- and copolymerization. These novel polymers with biological activity can be potentially useful for application in medicine, optoelectronics and photonics.
Keywords: 6-hydroxybenzofuran-3-one; 6-hydroxyaurones; methacrylates